An examination of the coincidence anticipation performance of soccer players according to their playing positions and different stimulus speeds - Saygin, O.; Goral, K.; Ceylan, H. I. (The Sport Journal, 2016)
The purpose of this study is to examine the coincidence anticipation timing of soccer players, according to different stimulus speeds and playing positions. Forty licensed soccer players (goalkeepers: 10, defense: 10; midfielder: 10, forward: 10) participated voluntarily in this study. Coincidence anticipation timing performances of the subjects at different stimulus speeds (3mph, 5mph, 8mph) were measured with a Bassin anticipation timer. In order to determine whether the coincidence anticipation timing performance values of the soccer players vary according to different stimulus speeds and player positions, the One-Way Anova Test was used. In order to find from which player position and stimulus speed the difference stemmed, the Tukey HSD Test was used. A significant difference was observed in the (3mph) stimulus speed absolute error score according to the player positions of the soccer players (p less than 0.05). The significant difference stems from the goalkeepers having less absolute error scores than defense and midfielder players and their statistically higher performance accuracy in coincidence anticipation timing. Significant differences were found between the absolute error scores at 3mph, 5mph, 8mph stimulus speeds (p less than 0.05), and it was observed that the absolute error score was less at lower stimulus speeds (3mph) when compared with higher stimulus speeds (8mph), and that the coincidence anticipation timing performance accuracy was better. As a conclusion, it is recommended that activities that improve coincidence anticipation timing of the soccer players at different stimulus speeds should be included when training programs are planned.